Compaction, strength and dissolution characteristics of urea 46% N tablets - Shamsudin, Intan Soraya (2014)
Lab scale urea tablets are formed through direct compaction by uniaxial die compaction method. The main objectives of this study are 1) to investigate the effect of particle size on the compaction properties and characteristics of urea tablets, 2) to evaluate the influence of die wall lubrication on the compaction properties and characteristics of urea tablets and 3) to determine the influence of admixed lubrication on the compaction properties and characteristics of urea tablets. The particle sizes were varying in the form of granules and powders for urea granules tablets (TG tablets) and urea powder tablets (TP tablets). The lubricants;magnesium stearate (MgSt) and stearic acid were lubricated on the surfaces of the die wall and admixed in the formulation at compositions of 1%, 3%, 5% and 10% w/w. The compaction process was conducted at five applied pressures ranging between 37.67 MPa and 188.35 MPa using a universal testing machine. The compaction properties, namely plastic work, elastic work, friction work and maximum ejection pressure were analyzed from the force-displacement profile of the compaction process. Characteristics of the urea tablets were tested for the compressive strength and ammonium ion release through dissolution test. From the different particle sizes experimental results obtained, it was found that TG tablets deformed more by fragmenting deformation under applied pressure according to the high plastic work and low compressive strength. TP tablets deformed more by plastic deformation under applied pressure based on the high plastic work and high compressive strength. The TG tablets had lower ammonium ion release than urea granules at all applied pressures. They also had lower ammonium ion release than TP tablets at almost all applied pressures except 75.34 MPa. The results of die wall lubrication have shown the tablets die wall lubricated with stearic acid had lower plastic work and maximum ejection pressure. However, they had higher elastic work and friction work. They produced high strength tablets and lower ammonium ion release than urea granules and other tablets when formed at 75.34 and 113 MPa. From the admixed lubrication results, most of the tablets had good compaction properties, possessed high compressive strength and release lower ammonium ion when formed at applied pressures from 113 to 188.35 MPa. The amount of lubricant used was less than 1% w/w and stearic acid as the choice of the lubricant. As a conclusion, this preliminary study provides information concerning the tablets forming ability, choosing the suitable form of materials and the influence of lubricant through die wall and admixed lubrication in direct compaction of urea.